Question

Asked Sep 4, 2019

-3(x+9)=-48

Step 1

Given information:

The given equation is

Step 2

Calculation:

First, we apply the distributive property a...

Tagged in

Q: how do i solve by factoring: 4(x-2)/x-3 +3/x=-3/x(x-3)

A: LCM= x(x-3)We multiply both sides by LCM and distribute it.

Q: How is 1/2 (x+5)-4=1/3 (2x-1) solved for an answer?

A: The given equation is 1/2(x+5) -4 = 1/3(2x-1).

Q: There are 56 students in a speech contest. Yesterday 1/4 of them gave their speeches. Today 2/7 of t...

A: Click to see the answer

Q: what are the blanks

A: It is given that additional of 1 worker increases production by 0.12.55 workers is a 5 worker increa...

Q: Simplify #28

A: The known fact is that

Q: how to solve 5/7m-1/2=3/5

A: Refer to the question. We have to find the value of m for the given equation.

Q: When Fritz drives to work his trip takes 30 minutes but when he takes the train a takes 20 minutes f...

A: Refer to the question, we need to find the distance he travels to work.The time taken when Fritz dri...

Q: Factoring out a constant before factoring a quadratic. Factor completely 2y2-22y+48 Can someone plea...

A: Given,

Q: How to solve |2y-3| = |17-3y|

A: |2y-3| = |17-3y|When we remove the absolute sign there are two possible cases. 2y-3=17-3y or 2y-3= ...